Molecular Characterization of the Oncogene BTF3 and Its Targets in Colorectal Cancer - Wang, Hantao; Xing, Junjie; Wang, Wei; Lv, Guifen; He, Haiyan; Lu, Yeqing; Sun, Mei; Chen, Haiyan; Li, Xu (Frontiers in Cell and Developmental Biology, 2021)
Colorectal cancer (CRC) is one of the most commonly diagnosed and leading causes of cancer mortality worldwide and the prognosis of patients with CRC remains unsatisfactory. Basic Transcription Factor 3 (BTF3) was an oncogene and hazardous prognosticator in CRC. Although two distinct functional mechanisms of BTF3 in different cancer types are reported, its role in CRC still not clear. In this study, we aim to performed molecular characterization of oncogene BTF3 regulator and its targets in colorectal cancer. Here, we first identified the transcriptional targets of BTF3 by applying combined RNA-Seq and ChIP-Seq analysis, following identified CHD1L as a transcriptional target of BTF3. Thereafter, we conducted immunoprecipitation (IP)-MS and E3 ubiquitin ligase analysis to identify potential interacting targets of BTF3 as a subunit of Nascent-Polypeptide-Associated Complex (NAC). The analysis found that BTF3 might also inhibit E3 ubiquitin ligase HERC2 mediated p53 degradation. At last, miRNAs targeting BTF3 were predicted and validated. Decreased miR-497-5p expression is responsible for higher level of BTF3, post-transcriptionally. Collectively, we concluded that BTF3 is an oncogene, and there may exists a transcription factor and NAC related proteolysis mechanism in CRC. This study would provide a comprehensive basis for understanding the oncogenic mechanism of BTF3 in CRC.